Effect of Zr content on microstructure and mechanical properties of AlCoCrFeNi high entropy alloy. (15th March 2016) - Chen, Jian; Niu, Pengyun; Liu, Yunzi; Lu, Yukun; Wang, Xianhui; Peng, Yuli; Liu, Jiangnan
Abstract: The AlCoCrFeNiZr x alloys are produced by electric arc melting and their microstructure and mechanical properties were analyzed. The alloys present two types of microstructures. One is a periodic structure consisting of the ordered BCC phase and BCC solid solution phase caused by spinodal decomposition, and the other is a mixture of the ordered BCC phase and Laves phase which nucleate and grow alternatively. The coexistence of ordering and spinodal decomposition can be attributed to the lattice strain caused by the addition of Zr element with a large atom radius. The criteria (ΔHmix and ΔR) cannot effectively predict the phases for the AlCoCrFeNiZr x alloys and the Laves phase even appears in the AlCoCrFeNiZr0.008 alloy. The compressive test shows that minor Zr addition can significantly improve the mechanical properties. The AlCoCrFeNiZr0.008 alloy has the yield strength of 1560 MPa, fracture strength of 3513 MPa and plastic strain of 29.5%, which are increased by 240 MPa, 843 MPa and 7% compared with the AlCoCrFeNi alloy, respectively. However, when the Zr content is above 0.1, the fracture strength and plastic strain decrease significantly although the yield strength of the alloys increases with the Zr content further increasing. Graphical abstract: Highlights: Minor Zr addition significantly increases mechanical property of AlCoCrFeNi. The criteria (ΔHmix and ΔR) cannot predict phases of AlCoCrFeNiZr x . Volume fraction of Laves phase increases with Zr content increasing.